1998
DOI: 10.2337/diab.47.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein ε2 Allele With Diabetic Nephropathy in Caucasian Subjects With IDDM

Abstract: Epidemiological and family studies imply that genetic factors are important in the etiology of diabetic nephropathy in subjects with IDDM (1,2). Vascular disease is characteristic of nephropathy, and lipoproteins are important determinants of atherosclerosis. Apolipoprotein E (apoE) is a major protein constituent of lipoproteins, mediating hepatic lipoprotein uptake and reverse cholesterol transport. ApoE occurs as three isoproteins: E3 with normal function, E2 with reduced affinity, and E4 with increased affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 14 publications
7
38
1
Order By: Relevance
“…Several studies (72)(73)(74) concluded that the ApoE4 isoform is associated with protection from type 2 DN in both white and Japanese individuals. Hsu et al (70) corroborated this finding, demonstrating that the frequency of the 4 allele is decreased in type 2 diabetes and chronic kidney disease and revealing association between the 2 allele and chronic kidney disease, a result that is consistent with several older studies of type 1 DN in white individuals (75,76) and one of type 2 DN in Japanese individuals (77). In contrast, an equal number of studies (78 -80) failed to find any association between 2 and type 2 DN or microvascular complications associated with type 2 diabetes.…”
Section: Additional Candidate Genes Of Interestsupporting
confidence: 79%
“…Several studies (72)(73)(74) concluded that the ApoE4 isoform is associated with protection from type 2 DN in both white and Japanese individuals. Hsu et al (70) corroborated this finding, demonstrating that the frequency of the 4 allele is decreased in type 2 diabetes and chronic kidney disease and revealing association between the 2 allele and chronic kidney disease, a result that is consistent with several older studies of type 1 DN in white individuals (75,76) and one of type 2 DN in Japanese individuals (77). In contrast, an equal number of studies (78 -80) failed to find any association between 2 and type 2 DN or microvascular complications associated with type 2 diabetes.…”
Section: Additional Candidate Genes Of Interestsupporting
confidence: 79%
“…Two previous studies (n = 162 and 252) did, however, find an association [17,19]. Two out of three studies in patients with Type II (non-insulin-dependent) diabetes mellitus found that the e2 allele was associated with increased risk of nephropathy [31,39,40].…”
Section: Discussionmentioning
confidence: 82%
“…Because the e2 allele is associated with an increased concentration of triglyceride [15,16] it is a candidate gene for the development of nephropathy. Three small studies in Type I diabetic patients have found conflicting evidence on whether the e2 allele is a risk factor for nephropathy [17,18,19]. Therefore in this study we also examined whether the e2 allele is associated with albuminuria, cross-sectionally and prospectively.…”
mentioning
confidence: 99%
“…Recently, this ⑀2/⑀3/⑀4 polymorphism of APOE has been investigated for the association with DN in subjects with both type 1 and type 2 diabetes using a case-control comparison, but the findings were inconclusive (7)(8)(9)(10)(11)(12)(13)(14)(15). Very recently, we reported that the ⑀2 allele of APOE increases the risk of DN in type 1 diabetes in a large number of case-control comparisons and a family-based study called the transmission/disequilibrium test (16).…”
mentioning
confidence: 99%